An environmentally friendly electrolyte for preparing a high-density structural corrosion-resistant coating on a magnesium alloy surface and its application

By using neutral electrolyte and constant voltage DC pulse power supply for microarc oxidation on the surface of magnesium alloy, the problems of poor density and environmental pollution of magnesium alloy coating are solved, and the high density and corrosion resistance are improved, which is suitable for industrial production. .

CN115418697BActive Publication Date: 2024-12-17NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211165107.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-23
Publication Date
2024-12-17
Estimated Expiration
2042-09-23

AI Technical Summary

Technical Problem

The electrolyte during microarc oxidation of existing magnesium alloys has problems such as high surface roughness, poor density, large void ratio, poor economics of the electrolyte and environmental pollution, especially the corrosion resistance of ZrO2 coating under zirconium salt system. .

Method used

Using a neutral electrolyte consisting of 6g/L of ammonium fluorozirconate, 4g/L of sodium dihydrogen phosphate, 1g/L of sodium fluoride, and 1g/L of sodium hydroxide, to reduce fluorozirconium by controlling the pH value in the neutral range. The amount of ammonium acid, phosphate and fluoride is used to reduce ion concentration, avoid ablation, improve the density and corrosion resistance of ZrO2-MgO ceramic coating, and adopt a constant voltage DC pulse power supply for microarc oxidation treatment.

Benefits of technology

A ZrO2-MgO corrosion-resistant coating with low surface roughness and uniform surface roughness is generated, which improves the corrosion resistance of magnesium alloys, reduces preparation costs, and reduces environmental pollution. It has the advantages of green and environmental protection, safety and harmlessness, and is suitable for industrial production. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115418697B_ABST
    Figure CN115418697B_ABST
Patent Text Reader

Abstract

The invention discloses an environmentally friendly electrolyte for preparing a high-density structure corrosion-resistant coating on the surface of a magnesium alloy, which is composed of the following components: 6g / L-9g / L of ammonium fluorozirconate, 4g / L of sodium dihydrogen phosphate, 1g / L of sodium fluoride, 1g / L-2g / L of sodium hydroxide, and the rest is deionized water; the application of the electrolyte of the invention includes: 1. pre-treating the magnesium alloy; 2. preparing a neutral zirconium salt system solution as an electrolyte; 3. preparing a high-density structure ZrO2-MgO corrosion-resistant coating on the surface of the magnesium alloy by micro-arc oxidation. The electrolyte of the invention improves the compactness and corrosion resistance of the ZrO2-MgO corrosion-resistant coating by controlling the composition and content of each component, reducing the ion concentration, avoiding the occurrence of ablation, reducing costs and reducing environmental pollution, and being green and environmentally friendly; the invention adopts micro-arc oxidation to prepare a corrosion-resistant coating with a continuous and dense structure, no through holes, and good corrosion resistance, thereby improving the preparation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium alloy surface treatment, and specifically relates to an environmentally friendly electrolyte for preparing a high-density structure corrosion-resistant coating on a magnesium alloy surface and application thereof. Background Art

[0002] Magnesium alloys have the advantages of high specific stiffness, specific strength, good shock absorption, electromagnetic shielding performance, etc., and are widely used in the defense industry and civilian fields. Magnesium alloys are highly chemically active and prone to corrosion failure, so magnesium alloy products usually require surface protection treatment. In recent years, in the surface protection of magnesium alloy products such as wheels, firearms, magnesium communication equipment housings, outdoor LED housings, 3C products, etc., micro-arc oxidation has been used for surface treatment at home and abroad, and certain progress has been made. Micro-arc oxidation technology has simple processing technology, low cost, and little impact on the environment. It is suitable for various complex workpieces. Since the film layer is grown in situ on the substrate, the obtained ceramic coating has excellent bonding performance with the substrate, excellent wear resistance, and strong corrosion resistance, making it stand out among many methods.

[0003] At present, common electrolytes for micro-arc oxidation of magnesium alloys are silicate systems, aluminate systems, and phosphate systems. Although the prepared ceramic layer can effectively protect the substrate and improve its corrosion resistance and wear resistance, they all have their own problems, such as high surface roughness, thin film thickness, and pollution to the water environment. As the application scope of magnesium alloys continues to expand and the application environment conditions continue to become more stringent, the requirements for the corrosion resistance and wear resistance of its protective coating are becoming higher and higher. In recent years, the ZrO2 micro-arc oxidation coating generated in the zirconium salt system has received more attention, but the coating obtained by the existing preparation process also has some problems such as high roughness, large porosity, poor density, and poor economic efficiency of the electrolyte. For example, the ZrO2 coating prepared by the electrolyte system used in the patent with publication number CN101994145A has a high surface roughness, Ra of 0.76μm to 0.95μm. In addition, the amount of fluoride used in the electrolyte is relatively large, reaching 2g / L to 8g / L, which causes great pollution to the environment; while the zirconium salt content in the electrolyte used in the patent with publication number CN102345151A is as high as 30g / L, and the amount of zirconium salt used is relatively large. Considering the high price of zirconium salt, this formula is not very suitable for engineering applications. In addition, the pH values ​​in the electrolyte embodiments are acidic or alkaline, which will also cause certain pollution to the environment. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an environmentally friendly electrolyte for preparing a high-density structural corrosion-resistant coating on the surface of a magnesium alloy in view of the deficiencies of the above-mentioned prior art. The electrolyte improves the compactness of the ZrO2-MgO corrosion-resistant coating by controlling the composition and content of each component to ensure that the pH of the electrolyte is about neutral. Combined with reducing the amount of ammonium fluorozirconate, phosphate and fluoride in the electrolyte to reduce the ion concentration and avoid the occurrence of ablation, the compactness and corrosion resistance of the ZrO2-MgO ceramic coating are improved, the cost is reduced, and the environmental pollution is reduced, which is green and environmentally friendly.

[0005] To solve the above technical problems, the technical solution adopted by the present invention is: an environmentally friendly electrolyte for preparing a high-density structural corrosion-resistant coating on the surface of a magnesium alloy, characterized in that it consists of the following components: 6g / L~9g / L of ammonium fluorozirconate, 4g / L of sodium dihydrogen phosphate, 1g / L of sodium fluoride, 1g / L~2g / L of sodium hydroxide, and the rest is deionized water.

[0006] In the electrolyte of the present invention, the pH value of the electrolyte is ensured to be about neutral by controlling the composition and content of each component. The arc discharge of micro-arc oxidation in the neutral electrolyte is more uniform and dense, thereby improving the compactness of the ZrO2-MgO corrosion-resistant coating. At the same time, since the arc discharge in the electrolyte with high ion concentration is fierce, it is easy to ablate the substrate and the coating, and the magnesium alloy itself is more active and more prone to ablation. The amount of ammonium fluorozirconate, phosphate and fluoride in the electrolyte of the present invention is significantly reduced, the ion concentration in the electrolyte is reduced, the occurrence of ablation is avoided, and it is beneficial to the surface of the magnesium alloy. The surface is subjected to micro-arc oxidation to generate a dense and uniform ZrO2-MgO ceramic coating, thereby improving its corrosion resistance; in addition, the amount of ammonium fluorozirconate used in the electrolyte of the present invention is significantly reduced, which effectively reduces the preparation cost, greatly improves the economy of the electrolyte, and is conducive to industrial production, and the amount of phosphate and fluoride used in the electrolyte is also significantly reduced, thereby reducing the pollution to the environment caused by subsequent waste liquid treatment, and has the advantage of being green and environmentally friendly; compared with the acidic or alkaline solutions in the prior art, the electrolyte of the present invention does not contain toxic ions and heavy metal ions, and has the advantage of being safe and harmless.

[0007] The above-mentioned environmentally friendly electrolyte for preparing a high-density structural corrosion-resistant coating on the surface of a magnesium alloy is characterized by being composed of the following ingredients: 6 g / L ammonium fluorozirconate, 4 g / L sodium dihydrogen phosphate, 1 g / L sodium fluoride, 1.5 g / L sodium hydroxide, and the rest being deionized water.

[0008] In addition, the present invention also discloses an application of the above-mentioned environmentally friendly electrolyte for preparing a high-density structure corrosion-resistant coating on the surface of a magnesium alloy, characterized in that the application method comprises the following steps:

[0009] Step 1: Use 180#, 600#, 800#, 1200#, 1500# water-resistant abrasive paper and metallographic sandpaper to polish the magnesium alloy step by step, then place it in a metal cleaning agent for ultrasonic degreasing at room temperature for 5 minutes, use hot water and cold water to clean it respectively, then place it in anhydrous ethanol ultrasonic cleaning for 10 minutes, dry it for standby use, and complete the pretreatment;

[0010] Step 2: Add ammonium fluorozirconate, sodium dihydrogen phosphate, sodium fluoride, and sodium hydroxide to deionized water in sequence and continue stirring until completely dissolved to prepare a neutral zirconium salt system solution, and then place the neutral zirconium salt system solution in an electrolytic cell and let it stand as an electrolyte;

[0011] Step three, clamp the magnesium alloy pretreated in step one with a fixture, place it in an electrolytic cell, and completely immerse it in the electrolyte as an anode, use a stainless steel sheet as a cathode, and then perform micro-arc oxidation treatment to prepare a high-density structure ZrO2-MgO corrosion-resistant coating on the surface of the magnesium alloy; the micro-arc oxidation treatment uses a constant voltage DC pulse power supply.

[0012] The present invention adopts an environmentally friendly electrolyte to perform micro-arc oxidation treatment on the surface of the magnesium alloy, and obtains an in-situ grown ZrO2-MgO corrosion-resistant ceramic coating on the surface of the magnesium alloy. By adopting a constant-voltage DC pulse power supply and stabilizing voltage control in a low-voltage area, the ZrO2-MgO corrosion-resistant coating is promoted to grow denser in the initial stage of micro-arc oxidation.

[0013] The above application is characterized in that the metal cleaning agent in step 1 is a neutral metal cleaning agent with a mass concentration of 5%. Based on the characteristics of magnesium alloys being high in activity and poor in corrosion resistance and corroding in both acidic and alkaline environments, it is preferred to use a neutral metal cleaning agent to avoid corrosion of the magnesium alloy substrate.

[0014] The above application is characterized in that the pH of the neutral zirconium salt system solution in step 2 is 6.5-7.5, and sodium hydroxide is used to adjust the pH. By using the above neutral zirconium salt system solution, the uniformity and density of arc discharge of micro-arc oxidation are improved, thereby improving the density of ZrO2-MgO corrosion-resistant ceramic coating. At the same time, the neutral zirconium salt system solution is more environmentally friendly and safe, and does no harm to human skin.

[0015] The above application is characterized in that the process parameters of the micro-arc oxidation treatment in step 3 are: voltage 400V-450V, frequency 500Hz, duty cycle 15%, time 10min-15min, and a refrigerator is used to control the temperature of the electrolyte to 18°C-25°C during the micro-arc oxidation treatment. By controlling the process parameters of the micro-arc oxidation treatment, it is possible to avoid the coating being ablated and rough due to excessive voltage, and the coating being too thin due to too low voltage and unable to achieve a high-density structure, thereby ensuring that all properties of the coating are optimal; the present invention controls the temperature of the electrolyte during the micro-arc oxidation process to avoid ablation of the coating at high temperature, surface roughness, and even large-diameter holes, thereby affecting the corrosion resistance of the coating.

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] 1. The present invention controls the composition and content of each component to ensure that the pH of the electrolyte is about neutral, so that the arc discharge of micro-arc oxidation is more uniform and dense, thereby improving the density of the ZrO2-MgO corrosion-resistant coating. Combined with reducing the amount of ammonium fluorozirconate, phosphate and fluoride in the electrolyte to reduce the ion concentration and avoid the occurrence of ablation, it is beneficial to form a dense and uniform ZrO2-MgO ceramic coating on the surface of the magnesium alloy through micro-arc oxidation, thereby improving its corrosion resistance.

[0018] 2. Compared with the electrolyte in the prior art, the amount of ammonium fluorozirconate, phosphate and fluoride in the electrolyte of the present invention is significantly reduced, and it does not contain toxic ions and heavy metal ions, which greatly improves the economy of the electrolyte and reduces the pollution to the environment caused by subsequent waste liquid treatment. It is green, environmentally friendly, safe and harmless, and is conducive to industrial production.

[0019] 3. The present invention adopts a micro-arc oxidation method to in-situ grow a ZrO2-MgO corrosion-resistant coating on the surface of a magnesium alloy. The surface roughness of the ZrO2-MgO corrosion-resistant coating is low (Ra = 0.5 μm to 0.7 μm), the coating structure is continuous and dense without through holes, and the corrosion resistance is good. The corrosion current density in a 3.5% NaCl solution is 3.247×10 -8 A / cm 2 , which solves the problems of rough surface, low density and poor corrosion resistance of the coatings currently prepared by micro-arc oxidation of magnesium alloys in a zirconium salt system.

[0020] 4. Compared with the micro-arc oxidation process parameters in the prior art, the micro-arc oxidation time of the present invention is shorter, which improves the preparation efficiency of the coating and has the advantages of high efficiency and energy saving.

[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a macroscopic morphology of the ZK61M magnesium alloy with a highly dense ZrO2-MgO corrosion-resistant coating in Example 1 of the present invention.

[0023] Figure 2 This is a surface scanning electron microscope image of the ZK61M magnesium alloy having a highly dense structure ZrO2-MgO corrosion-resistant coating in Example 1 of the present invention.

[0024] Figure 3 This is a scanning electron microscope image of the interface of the ZK61M magnesium alloy having a highly dense ZrO2-MgO corrosion-resistant coating in Example 1 of the present invention.

[0025] Figure 4 This is a surface scanning probe microscope image of the ZK61M magnesium alloy having a highly dense ZrO2-MgO corrosion-resistant coating in Example 1 of the present invention.

[0026] Figure 5 This is a surface scanning probe microscope image of the ZK61M magnesium alloy having a highly dense structure ZrO2-MgO corrosion-resistant coating in Example 2 of the present invention.

[0027] Figure 6 This is the X-ray diffraction analysis spectrum of the high-density ZrO2-MgO corrosion-resistant coating prepared on the surface of ZK61M magnesium alloy in Examples 1 and 2 of the present invention.

[0028] Figure 7 The electrochemical polarization curves of the ZK61M magnesium alloy and the high-density ZrO2-MgO corrosion-resistant coating prepared on the surface of the ZK61M magnesium alloy in Examples 1 and 2 of the present invention in 3.5% NaCl solution are shown. DETAILED DESCRIPTION

[0029] Example 1

[0030] The environmentally friendly electrolyte of this embodiment is composed of the following ingredients: 6 g / L of ammonium fluorozirconate, 4 g / L of sodium dihydrogen phosphate, 1 g / L of sodium fluoride, 1.5 g / L of sodium hydroxide, and the rest is deionized water.

[0031] The application method of the environmentally friendly electrolyte in this embodiment includes the following steps:

[0032] Step 1, select a ZK61M magnesium alloy sheet with a size (length × width × thickness) of 15mm × 15mm × 3mm as a substrate, first use 180# water-resistant abrasive paper to polish and remove machining marks on the surface of the ZK61M magnesium alloy sheet, then use 600#, 800#, 1200#, 1500# water-resistant abrasive paper and metallographic sandpaper to polish the magnesium alloy step by step, place it in a neutral metal cleaning agent with a mass concentration of 5% for ultrasonic degreasing at room temperature for 5 minutes, use hot water and cold water to clean it respectively, then place it in anhydrous ethanol ultrasonic cleaning for 10 minutes, dry it for standby use, and complete the pretreatment;

[0033] Step 2: Add ammonium fluorozirconate, sodium dihydrogen phosphate, sodium fluoride, and sodium hydroxide to deionized water in sequence and continue stirring until completely dissolved, and use sodium hydroxide to adjust the pH to 6.5-7.5 to prepare a neutral zirconium salt system solution, and then place the neutral zirconium salt system solution in an electrolytic cell and let it stand as an electrolyte;

[0034] Step three, use a fixture to clamp the ZK61M magnesium alloy sheet that has been pretreated in step one, place it in an electrolytic cell, and completely immerse it in the electrolyte as an anode, use a stainless steel sheet as a cathode, and then perform micro-arc oxidation treatment to prepare a high-density structure ZrO2-MgO corrosion-resistant coating on the surface of the ZK61M magnesium alloy sheet to obtain a ZK61M magnesium alloy with a high-density structure ZrO2-MgO corrosion-resistant coating; the micro-arc oxidation treatment uses a constant voltage DC pulse power supply, and the process parameters of the micro-arc oxidation treatment are: voltage 400V, frequency 500Hz, duty cycle 15%, time 15min, and during the micro-arc oxidation treatment, a refrigerator is used to control the temperature of the electrolyte to 18°C ​​~ 25°C.

[0035] The high-density ZrO2-MgO corrosion-resistant coating prepared on the surface of ZK61M magnesium alloy in this example was subjected to energy spectrum EDS analysis, and the results are shown in Table 1 below.

[0036] Table 1

[0037] element Zr Mg O F Na P Zn Total Atomic ratio (%) 16.26 27.36 20.16 24.07 1.15 10.10 0.90 100

[0038] It can be seen from Table 1 that the ZrO2-MgO-Y2O3 composite ceramic coating prepared on the surface of the ZK61M magnesium alloy in this embodiment is composed of elements such as Zr, Mg, O, F, Na, P, and Zn.

[0039] Figure 1 The macroscopic morphology of the ZK61M magnesium alloy with a highly dense ZrO2-MgO corrosion-resistant coating in this embodiment is shown in FIG. Figure 1 It can be seen that the high-density structure ZrO2-MgO corrosion-resistant coating is grayish white with uniform color, complete morphology, and has no defects such as ablation, peeling, and cracking.

[0040] Figure 2 The surface scanning electron microscope image of the ZK61M magnesium alloy with a high-density ZrO2-MgO corrosion-resistant coating in this embodiment is shown in FIG. Figure 2 It can be seen that the number of micropores in the high-density structure ZrO2-MgO corrosion-resistant coating is small, the pore size is small, and the surface porosity is 7.076%, which is beneficial to improving the corrosion resistance of the coating.

[0041] Figure 3 The interface scanning electron microscope image of the ZK61M magnesium alloy with a high-density ZrO2-MgO corrosion-resistant coating in this embodiment is shown in FIG. Figure 3 It can be seen that the high-density structure ZrO2-MgO corrosion-resistant coating is tightly bonded to the ZK61M magnesium alloy substrate, the coating is highly dense and has no through holes, which is beneficial to enhancing the corrosion resistance of the coating.

[0042] Figure 4 The surface scanning probe microscope image of the ZK61M magnesium alloy with a high-density ZrO2-MgO corrosion-resistant coating in this embodiment is shown in FIG. Figure 4 It can be seen that the surface of the high-density structure ZrO2-MgO corrosion-resistant coating has fewer peak-like protrusions and lower heights, indicating that the coating surface is relatively smooth. The surface roughness Ra of the coating is measured to be 0.556 μm.

[0043] Example 2

[0044] The difference between this embodiment and implementation 1 is that the environmentally friendly electrolyte consists of the following ingredients: 9 g / L ammonium fluorozirconate, 4 g / L sodium dihydrogen phosphate, 1 g / L sodium fluoride, 2 g / L sodium hydroxide, and the rest is deionized water; the process parameters of the micro-arc oxidation treatment are: voltage 450 V, frequency 500 Hz, duty cycle 15%, time 10 min.

[0045] The high-density ZrO2-MgO corrosion-resistant coating prepared on the surface of ZK61M magnesium alloy in this example was subjected to energy spectrum EDS analysis, and the results are shown in Table 2 below.

[0046] Table 2

[0047] element Zr Mg O F Na P Zn Total Atomic ratio (%) 19.86 26.72 18.67 28.02 1.08 4.93 0.73 100

[0048] It can be seen from Table 2 that the ZrO2-MgO-Y2O3 composite ceramic coating prepared on the surface of the ZK61M magnesium alloy in this embodiment is composed of elements such as Zr, Mg, O, F, Na, P, and Zn.

[0049] Figure 5 The surface scanning probe microscope image of the ZK61M magnesium alloy with a high-density ZrO2-MgO corrosion-resistant coating in this embodiment is shown in FIG. Figure 5The measurement shows that the surface roughness Ra of the coating is 0.5693 μm and the surface porosity is 8.471%.

[0050] Figure 6 The X-ray diffraction analysis spectrum of the high-density ZrO2-MgO corrosion-resistant coating prepared on the surface of ZK61M magnesium alloy in Examples 1 and 2 of the present invention is shown in FIG. Figure 6 It can be seen that the phase structures of the high-density ZrO2-MgO corrosion-resistant coatings prepared on the surface of the ZK61M magnesium alloy in Example 1 and Example 2 mainly include ZrO2, MgO and MgF2.

[0051] Figure 7 The electrochemical polarization curves of the ZK61M magnesium alloy and the high-density ZrO2-MgO corrosion-resistant coating prepared on the surface of the ZK61M magnesium alloy in Examples 1 and 2 of the present invention in a 3.5% NaCl solution are shown in FIG. Figure 7 It can be calculated that the corrosion current I of the high-density ZrO2-MgO corrosion-resistant coating prepared on the surface of ZK61M magnesium alloy in Example 1 is corr =3.247×10 -8 A / cm 2 , Example 2 Corrosion current I of the high-density ZrO2-MgO corrosion-resistant coating prepared on the surface of ZK61M magnesium alloy corr =5.712×10 -8 A / cm 2 , which is 1.526×10 -4 A / cm 2 It has been reduced by 4 orders of magnitude, indicating that the high-density ZrO2-MgO corrosion-resistant coating has a more positive corrosion potential and a lower corrosion current, so that the corrosion resistance of the coating is greatly improved, and it plays a good corrosion protection role for the ZK61M magnesium alloy substrate.

[0052] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. An application of an environmentally friendly electrolyte for preparing a high-density structural corrosion-resistant coating on a magnesium alloy surface, characterized in that: The environmentally friendly electrolyte is composed of the following ingredients: 6g / L to 9g / L of ammonium fluorozirconate, 4g / L of sodium dihydrogen phosphate, 1g / L of sodium fluoride, 1g / L to 2g / L of sodium hydroxide, and the rest is deionized water; The method of the application comprises the following steps: Step 1: Use 180#, 600#, 800#, 1200#, 1500# water-resistant abrasive paper and metallographic sandpaper to polish the magnesium alloy step by step, then place it in a metal cleaning agent for ultrasonic degreasing at room temperature for 5 minutes, use hot water and cold water to clean it respectively, then place it in anhydrous ethanol ultrasonic cleaning for 10 minutes, dry it for standby use, and complete the pretreatment; Step 2: Add ammonium fluorozirconate, sodium dihydrogen phosphate, sodium fluoride, and sodium hydroxide to deionized water in sequence and continue stirring until completely dissolved to prepare a neutral zirconium salt system solution, and then place the neutral zirconium salt system solution in an electrolytic cell and let it stand as an electrolyte; the pH of the neutral zirconium salt system solution is 6.5 to 7.5, and sodium hydroxide is used to adjust the pH; Step three, clamp the magnesium alloy pretreated in step one with a fixture, place it in an electrolytic cell, and completely immerse it in the electrolyte as an anode, use a stainless steel sheet as a cathode, and then perform micro-arc oxidation treatment to prepare a high-density structure ZrO2-MgO corrosion-resistant coating on the surface of the magnesium alloy; the micro-arc oxidation treatment uses a constant voltage DC pulse power supply.

2. The use of an environmentally friendly electrolyte for preparing a high-density structure corrosion-resistant coating on a magnesium alloy surface according to claim 1, characterized in that: It is composed of the following ingredients: 6 g / L ammonium fluorozirconate, 4 g / L sodium dihydrogen phosphate, 1 g / L sodium fluoride, 1.5 g / L sodium hydroxide, and the rest is deionized water.

3. The use of an environmentally friendly electrolyte for preparing a high-density structural corrosion-resistant coating on a magnesium alloy surface according to claim 1, characterized in that: The metal cleaning agent in step 1 is a neutral metal cleaning agent with a mass concentration of 5%.

4. The use of an environmentally friendly electrolyte for preparing a high-density structure corrosion-resistant coating on a magnesium alloy surface according to claim 1, characterized in that: The process parameters of the micro-arc oxidation treatment in step three are: voltage 400V~450V, frequency 500Hz, duty cycle 15%, time 10min~15min, and during the micro-arc oxidation treatment, a refrigerator is used to control the temperature of the electrolyte to 18°C~25°C.

Citation Information

Patent Citations

  • Method for preparing ZrO2 compound ceramic film on surfaces of magnesium and magnesium alloy through microarc oxidization

    CN102345151A

  • Highly corrosion-resistant ceramic coating solution prepared through magnesium alloy surface micro-arc oxidation and application thereof

    CN101994145A

  • Electrolyte solution for directly preparing zinc containing coating on surface of medical magnesium alloy and micro-arc oxidation method

    CN107557839A